(untitled) (PETITUM, 2020)
The research aims to determine the implementation of the digital certificate mapping (plotting) policy in providing legal certainty for land rights. The research is empirical legal research. This research was conducted at the Data and Information Center of the Ministry of Agrarian and Spatial Planning/National Land Agency of Kendari City. The results showed that the implementation of digital certificate mapping (plotting) was carried out by inputting manual data of land certificates (both old certificates and newly issued certificates) into a digital registration map application based on Global Positioning System technology which aims to validate the correctness of certificate data. where the results will show the validity of the land parcel data according to the information in the certificate. In line with the negative land registration publication system with a positive tendency in Indonesia, plotting does not provide absolute legal certainty, but at least plotting can minimize the potential for land disputes that can arise in the future, including double or overlapping certificates Penelitian bertujuan untuk mengetahui implementasi kebijakan pemetaan sertifikat secara digital (plotting) dalam memberikan kepastian hukum terhadap hak atas tanah. Penelitian adalah penelitian hukum empiris. Penelitian ini dilakukan di Pusat Data dan Informasi Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional Kota Kendari. Hasil penelitian menunjukkan bahwa implementasi pemetaan sertipikat secara digital (plotting) dilakukan dengan menginput data manual sertipikat tanah ke dalam dalam aplikasi peta pendaftaran digital yang berbasis teknologi Global Positioning System yang bertujuan memvalidasi kebenaran dari data sertifikat yang mana hasilnya akan menunjukkan validitas data bidang tanah telah sesuai keterangan di sertifikat. Sejalan dengan sistem publikasi pendaftaran tanah negatif bertendensi positif, plotting belum memberikan kepastian hukum secara absolut akan tetapi setidaknya plotting dapat meminimalisir potensi sengketa tanah yang dapat timbul di kemudian hari diantaranya sertipikat ganda atau tumpang-tindih